Lina Beck Bernard: strabismic traveler in Argentina in the 19Th century - Crolla, Adriana Cristina (Revista Melibea, 2025)
For some years now, gender studies have been concerned with including the problematic of women travelers or migrants and their textualities, as well as their way of constructing alternative gazes to account for these positions. Studying the figure and writing of Lina Beck Bernard, traveler with particular edges in the territory of the Pampa gringa and resident for five years in Santa Fe, between 1858 and 1862, along with her husband, the colonization businessman Charles Beck, is presented as unavoidable in the research group of the Center for Comparative Studies of FHUC. A series of happy circumstances justify it: the discovery of sources, contact with a descendant and the translation and publication of Lina Beck Bernard. Trilogía narrativa y otros ensayos under the UNL imprint in 2018. The creation in 2019 of the Migration Studies Program named after this couple is one more reason to continue the initiated path, towards the diffusion and valorisation of their name and work in the study of women travellers in the national territory.